144PSevere hypovitaminosis D in metastatic gastric cancer patients from the Northern and Southern hemispheres: Data from the EXPAND phase III trial. (24th November 2019) - Obermannova, R; Valik, D; Hasenclever, D; Zdrazilova-Dubska, L; Hacker, U; Demlova, R; Selingerova, I; Lordick, F
Abstract: Background: Our primary goal was to evaluate the association between vitamin D (25-OHD) plasma levels and overall survival (OS) in metastatic gastric cancer patients receiving first-line chemotherapy in the international phase III EXPAND study (EudraCT 2007-004219-75). Here we report on 25-OHD plasma levels and OS according to geographic hemisphere of residence. Methods: 25-OHD pre-therapeutic plasma levels were measured in 630 patients using chemiluminescent immunoassay (Abbott Laboratories, Illinois). All patients were treated with chemotherapy based on capecitabine and cisplatin ± cetuximab. The Cox proportional hazard regression model was used to analyse the association between 25-OHD and survival in both treatment arms. Results: 549 and 73 patients were recruited in the Northern and Southern hemispheres, respectively. The majority had severe hypovitaminosis D at baseline prior to start of treatment. Only 9.2% of patients had a normal 25-OHD plasma levels (applying accepted criteria of 25-OHD insufficiency with plasma levels < 75 nmol/l; deficiency defined as < 50 nmol/l). Median 25-OHD plasma level was 38.2 nmol/l (IQR 25.8; 58.9) and mean was 43.5 nmol/l. Patients from the Southern versus Northern hemisphere had slightly higher 25-OHD levels (median 45.6 vs. 37.4 nmol/l; p = 0.0172; mean 48.92 vs. 42.74; p = 0.03 ). This difference persists when adjusting for season in a linear regression model. As expected, we observed the highest levels of 25-OHD in samples drawn during the summer season and the lowest values in winter. No proof for a negative impact of hypovitaminosis D on survival or treatment response was detected and no difference in OS was seen between patients from the Southern vs. Northern hemisphere (median 8.3 months [95%CI 7.4-10.6] vs. 10.5 [95%CI 9.4-11.3]; Hazard Ratio = 1.195; p = 0.2001). Conclusions: No prognostic value of vitamin D deficiency was found in the EXPAND cohort. However, the majority of patients with metastatic gastric cancer have a severe vitamin D deficiency with only minor differences comparing Southern versus Northern hemisphere of residency. Legal entity responsible for the study: Masaryk Memorial Cancer Institute. Funding: Masaryk Memorial Cancer Institute, University Leipzig. Disclosure: R. Obermannova: Advisory / Consultancy, Speaker Bureau / Expert testimony: Servier; Advisory / Consultancy, Research grant / Funding (self): Merck; Advisory / Consultancy, Speaker Bureau / Expert testimony: Eli Lilly. F. Lordick: Advisory / Consultancy, Speaker Bureau / Expert testimony: Amgen, AstraZeneca, Astellas, Biontech, BMS, Eli Lilly, Elsevier, Excerpta Medica, Imedex, Infomedica, Iomedico AG, Medscape, MedUpdate GmbH, Merck Sharp Dohme, Merck Serono, Oncovis Gmbh, Promedicis, Springer Nature Group, StreamedUp!, Zymeworks; Research grant / Funding (institution): BMS. All other authors have declared no conflicts of interest.